Tile Influence Of Emotional Intelligence On Morality Judgment Among Primry Sciiool Students In Tehran - Parsa, Nasrin Arian (2015)
A consideration of emotion has been in the context of teaching and education. This study focuses on the influence of Emotional intelligence on mental health and moral judgment among primary school students in Tehran. It is highly likely that emotionally intelligent students could provide help in how to manage emotions to control behavior individuals. Therefore, this research assessment emotional intelligence according to Baran (1997) and Salovey (1990) theories and relevance to Morality judgment by Kohlberg (1976) theory who have to deal with students coming to class with different feelings about learning, This study attempted to assess emotional intelligence and its relationship to morality judgment (one important belief that appears to have important effects on student outcomes) among Iranian students. Referring to research methodology if students develop their emotional intelligence, this will increase their levels of morality judgment. In addition, emotional intelligence and morality judgment were also examined with respect to gender. age.